2012
DOI: 10.1183/09031936.00125812
|View full text |Cite
|
Sign up to set email alerts
|

Delamanid improves outcomes and reduces mortality in multidrug-resistant tuberculosis

Abstract: Multidrug-resistant and extensively drug-resistant tuberculosis (TB) are associated with worse treatment outcomes for patients, including higher mortality, than for drug-sensitive tuberculosis. Delamanid (OPC-67683) is a novel anti-TB medication with demonstrated activity against multidrug-resistant disease.Patients who participated in the previously reported randomised, placebo-controlled trial of delamanid and the subsequent open-label extension trial were eligible to participate in a 24-month observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
251
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(268 citation statements)
references
References 25 publications
4
251
1
3
Order By: Relevance
“…In a phase 2 randomised controlled trial in patients with MDR tuberculosis, 376 treatment with delamanid resulted in higher rates of culture conversion at 2 months compared with placebo (45·4% vs 29·6%, p=0·008) after 8 weeks of treatment compared with placebo; the The Lancet Respiratory Medicine Commission carry-over observational study 377 showed higher rates of favourable treatment outcome in participants who received 6 months or more versus 2 months or less of delamanid treatment (74·5% vs 55%; p<0·001). 377 Delamanid causes moderate QT prolongation (10-15 ms) but is otherwise well tolerated.…”
Section: Nitroimidazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase 2 randomised controlled trial in patients with MDR tuberculosis, 376 treatment with delamanid resulted in higher rates of culture conversion at 2 months compared with placebo (45·4% vs 29·6%, p=0·008) after 8 weeks of treatment compared with placebo; the The Lancet Respiratory Medicine Commission carry-over observational study 377 showed higher rates of favourable treatment outcome in participants who received 6 months or more versus 2 months or less of delamanid treatment (74·5% vs 55%; p<0·001). 377 Delamanid causes moderate QT prolongation (10-15 ms) but is otherwise well tolerated.…”
Section: Nitroimidazolesmentioning
confidence: 99%
“…377 Delamanid causes moderate QT prolongation (10-15 ms) but is otherwise well tolerated. QT prolongation appears to be associated with concentrations of the DM-6705 metabolite.…”
Section: Nitroimidazolesmentioning
confidence: 99%
“…As it must be recognised, following current trends, Europe is unlikely to achieve elimination of the disease by the target date of 2050 [23,24], we urgently need new vaccines, as well as improved diagnostics [25,26] and new drugs [27][28][29]. With respect to economic considerations, the aim of the present study was to evaluate the costs associated with TB disease in order to determine whether they outweigh the investment needed to generate a new vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…12) Further, delamanid has shown anti-TB activity in patients with drug-sensitive TB 13) and in patients with MDR-TB, and is being specifically developed to treat MDR infections. 14,15) Delamanid has been approved as a new drug for the treatment of MDR-TB and has been launched onto the market in Europe and Japan.…”
mentioning
confidence: 99%